(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
Hollow concrete block (HCB) is one of the most fundamental materials in building and construction worldwide. Therefore, HCB has emerged as a viable alternative to traditional building materials likebrick. It is an excellent choice for constructing walls, pavements, and other masonry work construct a long-lasting structure. Today’s new world requires a green, eco-friendly, and sustainable world, and HCB can play a significant role in achieving that goal. HCB has superior thermal and fire resistance properties, greater strength, cost-effectiveness, and eco-friendliness. Only a small amount of construction in Bangladesh is done using HCBs. However, as sustainable structural technology advances, more frequent use of HCBs will be required. As a result, this article will provide a brief overview of the various applications of HCBs in Bangladesh, including the manufacturing process and its benefits and drawbacks. Specifically, this work investigates and compares the effect of different natural fine aggregates collected from different areas of Bangladesh on the mechanical properties of HCB. The fine aggregates used in this study came from the Dharala, Patgram, Lalmonirhat, and Someshwari rivers in Durgapur, Netrokona, Bangladesh. HCBs were manufactured using a hydraulic press machine and were constructed using mix design ratios of 1: 5: 1: 3 (Cement: Gravel Sand: Sylhet Sand: Crushed Stone), 1: 4.17: 1.67: 1.5 (Cement: Gravel Sand: Sylhet Sand: Crushed Stone), 1: 2.33: 2: 1.33 (Cement: Gravel Sand: Stone Dust: Crushed Stone), 1: 3.33: 2.33 (Cement: Gravel Sand: Stone Dust) and 1: 2.5: 1: 0.50 (Cement: Gravel Sand: Stone Dust: Crushed Stone) with water cement (W/C) ratio of 0.37. The specimens’ dimensions were chosen to be 390 mm x 190 mm x 100 mm. The specimens were tested for unit weight, water absorption, compressive strength, and tensile strength after 28 days of water curing. The results showed that HCBs made with different fine aggregates from the Dharala, Patgram, Lalmonirhat, and Someshwari rivers in Durgapur, Netrokona, Bangladesh, have different compressive strengths at 28 days, namely 978 PSI, 1604 PSI, 1267 PSI, 1162 PSI, and 2128 PSI. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(2), 2023, P 153-158